2012
DOI: 10.3922/j.psns.2012.2.09
|View full text |Cite
|
Sign up to set email alerts
|

Daily anticipatory rhythms of behavior and body temperature in response to glucose availability in rats.

Abstract: When food is available recurrently at a particular time of day, several species increase their locomotion in the hours that precede food delivery, a phenomenon called food anticipatory activity (FAA). In mammals, many studies have shown that FAA is driven by a food-entrained circadian oscillator (FEO) that is distinct from the light-entrained pacemaker in the suprachiasmatic nucleus of the hypothalamus. Few studies have investigated the effect of sugar ingestion on food anticipatory rhythms and the FEO. We aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
(46 reference statements)
1
3
0
Order By: Relevance
“…Also, feeding time can entrain the intrinsic oscillation of clocks in liver cells, similar to what occurs in central oscillators in the brain when entrained by light 15 . These previous findings support the understanding that circadian and metabolic systems are reciprocally regulated 14 , 16 - 18 .…”
Section: Introductionsupporting
confidence: 85%
“…Also, feeding time can entrain the intrinsic oscillation of clocks in liver cells, similar to what occurs in central oscillators in the brain when entrained by light 15 . These previous findings support the understanding that circadian and metabolic systems are reciprocally regulated 14 , 16 - 18 .…”
Section: Introductionsupporting
confidence: 85%
“…Their earlier work had shown mice developed nutrient-dependent FAA to sweetened meal [ 93 ], however, chronically protein deprived mice did not show anticipation for a single protein meal (this was also true for carbohydrate and fat). More recent research, however, has concluded glucose availability can produce FAA in rats [ 94 ]. Results here show FAA was due to restriction of calories alone with no evidence that equivalent levels of PR increased FAA.…”
Section: Discussionmentioning
confidence: 99%
“…The former pathway passed circuits via different B-mechanisms and then reached St4 ( Figure 13 B). The circadian positive and negative correlation shift emerged ( Figure 2 B) as contributing to the formation of more complex emotional mechanisms with a psychologically relevant BD [ 35 , 36 , 37 , 38 ] –BT [ 57 , 60 ] correlation. In contrast, the latter influenced the underlying basic mechanism because of the longitudinal effect in St2 but not St3, just after the dramatic change in home environment and when feeding times were reduced from three to two.…”
Section: Resultsmentioning
confidence: 99%